2014
DOI: 10.1002/pros.22817
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HepaCAM inhibits cell viability and motility through suppressing nucleus translocation of androgen receptor and ERK signaling in prostate cancer

Abstract: Our results suggested that HepaCAM acted as a tumor suppressor in prostate cancer. HepaCAM inhibited cell viability and motility which might be through suppressing the nuclear translocation of Androgen Receptor and down-regulating the ERK signaling. Therefore, it was indicated that HepaCAM may be a potential therapeutic target for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ERK1/2 acts as nearly 180 different molecules targets and regulates several diverse cellular functions such as cell growth, cell cycle, proliferation, cell death, cell apoptosis, cell adhesion and transcription [9]. In fact, the ERK1/2 plays the above roles in various cancers, such as breast cancer [10], colorectal cancer [11], prostate cancer [12] and lung cancer [13]. However, not all references support the role of activated ERKs in promoting tumorigenesis, and result consistent with the role in tumor suppression has been reported as well [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle dysregulation is a major factor in cancer cell growth ( 24 ). ERKs have a key role in promoting cell survival and cellular proliferation ( 25 , 26 ) and have been considered to be significant targets for cancer therapeutics ( 27 ). Evidence indicates that erianin affects cell cycle progression, evidenced by inhibition of gastric carcinoma SGC-7901 cell proliferation by blocking progression to S phase ( 28 ), and arresting progression at the G 2 /M phase in hepatocellular carcinoma Huh7 cells ( 23 ) and human colorectal cancer SW480 cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…3d and e ). The former encodes an early growth response TF related among others to lymphocyte development and endothelial cell growth and migration whose downregulation could play a role in the proliferation, metastasis, and progression of cancer cells [ 36 , 37 ], whereas the latter is a likely tumor suppressor gene which codes for a protein involved in cell motility [ 38 ]. Finally, panels F and G illustrate the misregulation of TCF7L1 and DNAJC12 , two significant targets of GATA3 linked to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%